2021
DOI: 10.3390/ijerph18094420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Myofascial Therapy on Pain and Functionality of the Upper Extremities in Breast Cancer Survivors: A Systematic Review and Meta-Analysis

Abstract: (1) Objective: The purpose was to analyze the effectiveness of myofascial therapy on musculoskeletal pain and functionality of the upper extremities in female breast cancer survivors, and to evaluate the changes in range of motion, quality of life, and mood state of these patients. (2) Methods: Systematic searches were performed on the MEDLINE/PubMed, Web of Science, Scopus, and Physiotherapy Evidence Databases for articles published until October 2020, in order to identify randomized controlled trials which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(161 reference statements)
0
5
0
Order By: Relevance
“…For humerothoracic movements, a recent review with meta‐analyses showed conflicting results for range of motion, assessed with clinical methods (e.g., goniometer) 20 . Beneficial effects of myofascial therapy were seen for abduction range of motion, but not for flexion, compared to placebo treatment or other interventions 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For humerothoracic movements, a recent review with meta‐analyses showed conflicting results for range of motion, assessed with clinical methods (e.g., goniometer) 20 . Beneficial effects of myofascial therapy were seen for abduction range of motion, but not for flexion, compared to placebo treatment or other interventions 20 .…”
Section: Discussionmentioning
confidence: 99%
“…For humerothoracic movements, a recent review with meta‐analyses showed conflicting results for range of motion, assessed with clinical methods (e.g., goniometer) 20 . Beneficial effects of myofascial therapy were seen for abduction range of motion, but not for flexion, compared to placebo treatment or other interventions 20 . These results should be interpreted with caution because of the low‐methodological quality of the included studies and the wide variety in myofascial techniques used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The axillary lymph node (ALN) status is crucial for predicting the clinical classification and decisions on treatment of early-stage breast cancer (EBC) and could be the primary indicator of locoregional recurrence [ 1 , 2 ]. Lymph node dissection can cause lymphedema, which can further contribute to pain, bloating, pressure, fatigue, and functional restriction [ 3 , 4 ]. To reduce the occurrence of lymphedema, sentinel lymph node biopsy (SLNB) is mainly used before surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, these two techniques are often combined to achieve a faster and better therapeutic outcome 15 . In recent years, soft tissue therapy, including myofascial release, trigger point therapy, and soft tissue mobilization, has gained increasing use, despite the fact that there are reports in the available literature showing that the role of these techniques is not fully explained 16 , 17 or their influence is limited 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%